Nutritional Status, Menstrual Cycle and Stress with Primary Dysmenorrhea - Nurul Oktaviani; Isti Istianah (Jurnal Ilmiah Kesehatan (JIKA), 2022)
Primary dysmenorrhea is pain during menstruation and is not based on pathological conditions. Women in Indonesia experience primary dysmenorrhea. The incidence of primary dysmenorrhea in Jakarta is high. Study to analyze a relationship between nutritional status, menstrual cycle, stress level, and primary dysmenorrhea in class XI students at SMA Suluh, South Jakarta. Research is quantitative design cross-sectional. 60 sampling female students technique purposive random sampling. Data collection used anthropometric measurements and primary dysmenorrhea questionnaires, menstrual cycle questionnaires, and Depression Anxiety and Stress Scale (DASS). Data were analyzed using univariate analysis and bivariate data analysis using Chi-square. Results characteristics menstrual subjects were obtained 1x/month 58 (96,7%). Duration menstruation was 3-7 days 49 (81,7%). Primary dysmenorrhea at the beginning of menstruation was 53 (88,3%). 35 students (58,3%) experienced dysmenorrhea first time 6 months of menstruation. Duration menstrual pain 1-3 days 60 (100%). The primary dysmenorrhea scale of moderate pain was 29 (48,3%). 35 students (58,3%) did not experience back pain. 34 (56,7%) students experienced low back pain. Results of statistical analysis showed there was a significant relationship between nutritional status and primary dysmenorrhea p-value=0,00. The significant relationship between the menstrual cycle and primary dysmenorrhea p-value=0,03, and there was no relationship between stress levels and primary dysmenorrhea p-value=0,44. It can be concluded that there is a significant relationship between nutritional status and menstrual cycle and dysmenorrhea, but there is no significant relationship between stress levels and primary dysmenorrhea in class XI SMA Suluh Jakarta Selatan students.